Flexible and tandem quantum-dot light-emitting diodes with individually addressable red/green/blue emission - Qiang Su (Nature Portfolio, 2021)
Abstract Tandem quantum-dot light-emitting diodes (QLEDs) with multiple QLED elements vertically connected by the intermediate electrodes offer the advantages of high brightness and long lifetime. However, it is challenging to individually address each QLED element in conventional tandem structures. To address this challenge, here, transparent QLEDs built on flexible plastic substrates are developed as the building blocks for the tandem QLEDs. By vertically integrating a red, a green, and a blue transparent QLEDs with an ultraviolet glue, the resultant tandem QLED can emit separately controllable red/green/blue (R/G/B) emission with an external quantum efficiency (EQE) of 12.0%/8.5%/4.5%, respectively. Enabled by the transparent and extractable IZO electrodes, the QLED elements can also be connected in series or in parallel with an EQE of 24.8% or 8.2%, respectively. Our work provides a new implementation strategy for the realization of tandem QLEDs with individually addressable R/G/B emission for both display and lighting applications.